2005
DOI: 10.1080/09585190500298370
|View full text |Cite
|
Sign up to set email alerts
|

Performance pay in Canadian and Australian firms: a comparative study

Abstract: Based on data from 315 Canadian and Australian firms, this study examines the incidence of 13 specific forms of performance pay, along with factors that may affect their incidence. Overall, Canadian and Australian firms showed similar incidences of most forms of performance pay, with employee profit sharing the notable exception. Depending on the type and form of performance pay, various factors predicted the incidence of performance pay. As expected, firm size and unionization were among the most important pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Finally, profit-sharing systems may be more successful in creating a mutuality of interest when the group under the profit-sharing system is small and cohesive. However, empirical research has invariably found that profit-sharing systems are more common in larger organizations, possibly due to large fixed set-up costs (Kruse 1993;Long and Shields 2005). Nevertheless, since the proposition related to membership size has been central in much of the literature, we include it in our analysis.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Finally, profit-sharing systems may be more successful in creating a mutuality of interest when the group under the profit-sharing system is small and cohesive. However, empirical research has invariably found that profit-sharing systems are more common in larger organizations, possibly due to large fixed set-up costs (Kruse 1993;Long and Shields 2005). Nevertheless, since the proposition related to membership size has been central in much of the literature, we include it in our analysis.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…A number of studies have found a negative association between union recognition for collective bargaining and the adoption of variable pay linked to appraisal ( e.g. Gunnigle et al ., 1998; Long and Shields, 2005). Although a rise in individualist PPMS has taken place in unionised as well as non‐union workplaces ( e.g.…”
Section: Variations In Pay and Performance Management Approachesmentioning
confidence: 99%
“…In terms of the cross-regional studies, it was notable that a few articles assessed the extent to which HRM practices from the 'ideal types' of market economies (Hall and Soskice 2001) were converging towards each other (Carr and Pudelko 2006;Pudelko 2006). Similarly, it was explored whether, for instance, pay practices across liberal market economies were becoming more identical (Long and Shields 2005). The majority of studies with a regional focus concentrated on the European economic region (8), while the remainder was within Asia (4).…”
Section: Thematic Focimentioning
confidence: 99%